Análisis estructural de puentes atirantados, aplicación - Villoslada Trujillano, Manuel (2004)
This work is aimed at the study of bridges tensioned, using different methods of analysis such as the matrix, finite element and uria introduction to the plastic analysis, was used as tools the SAP2000 program, the Math Cad programming language and sheet of spreadsheet Excel for the case of lines. influence and verifications; Although the present study not plays in depth some topics as it not...: linearity of them elements structural, however shows bases for subsequent works of research. As applied to this study included the analysis of the Atumpampa bridge, located in the road Fernando Belaunde Ferry on the river Cumbaza, Morales district, province and Region San Martín, the projected bridge has a length of 84.00 meters. The novelty of - this system is to present new versions or types of bridges to save large spans, unless they require support i.ntermedios being a drawback in the rivers of...